La fontana della Piazza di Castel Gandolfo - Progetto di salvaguardia e recupero di valore artistico originario della Fontana berniniana - Mario Caporale; Antonino Tinè; Elisabetta Cicerchia (Archeomatica, 2018)
This article sketches the activities undertaken by the experts of the Rotary Club Roma Castelli Romani aimed at safeguard and recuperate the original artistic value of the Fountain of Piazza Castel gandolfo. Utilizing modern 3D scanning techniques a first phase have seen the analysis of the fountain in order to better understand the decay reasons of the stone and in order to reconstruct the border profiles for a subsequent phase of restauration. New promising techniques of restauration will be considered.